Predictive factors of hand radiographic lesions in systemic sclerosis: a prospective study. Issue 4 (3rd December 2010) - Avouac, J; Mogavero, G; Guerini, H; Drapé, J L; Mathieu, A; Kahan, A; Allanore, Y
Abstract : Objective: To examine the outcomes of hand radiographic x-rays in patients with systemic sclerosis (SSc) and to identify risk factors for the progression of hand radiographic lesions in a prospective cohort. Methods: Dual time-point x-rays were systematically performed after a median interval of 5 years (range 4–7 years) in 103 consecutively recruited patients with SSc. Univariate and multivariate Cox proportional hazards models evaluated predictors of progression of hand radiographic lesions. Results: Radiographic progression of erosive arthritis, acro-osteolysis, calcinosis and flexion contracture occurred in 24, 22, 27 and 18 patients, respectively. Multivariate Cox regression analysis did not identify any predictor of the progression of erosive arthritis. Digital ulcers were shown independently to predict the progression of acro-osteolysis and calcinosis (HR 12.43, 95% CI 1.97 to 88.40 and 3.16, 95% CI 1.22% to 9.43%, respectively). The diffuse cutaneous subset was shown to be an independent predictor of the progression of flexion contracture (HR 7.52, 95% CI 1.21 to 43.93). Conclusion: The results highlight the striking level of hand radiographic lesions in SSc and suggest close monitoring of patients with the diffuse cutaneous subset for the occurrence or worsening of this complication. The results also show that severe peripheral vascular involvement predicts both acro-osteolysis and calcinosis, highlighting their vascular background.